Static anisotropic fluid spheres in general relativity with nonuniform density - Singh T.; Singh G.P.; Srivastava R.S. (My University, 2025)
An Ansatz developed by Maharaj and Maartens is used to obtain solutions of Einstein's field equations for static anisotropic fluid spheres with nonuniform density. These solutions are matched with the Schwarzschild exterior solution. © 1991 Plenum Publishing Corporation.